The The Efficacy of an Engineered Biocarbon in Young Broiler Chicken During an Aflatoxin Exposure - Bayir, HO; Ritz, C; Fowler, J (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was conducted to evaluate aflatoxin (AFB1) adsorption capacity of a carbonaceous biomass (Bio-C) in vitro and the efficacy of a Bio-C in mitigating the effects of a 0.5 mg/kg dose of aflatoxins (AF) in vivo. In vitro AFB1 affinity of Bio-C were determined by using different AFB1 concentration containing solutions, and these concentrations were measured by a UV-visible spectrophotometry. In in vivo test, a total of 192 Cobb-500 male broilers were obtained on the day of hatch and randomly allocated to one of 32 treatments pens (6 birds/pen). Birds were fed a broiler starter mash diet containing either 0 or 0.5 mg/kg AF, with or without 0.4% of Bio-C, resulting in 4 treatments arranged as a 2x2 full-factorial. Pen weights and feed consumed were recorded weekly, and mortality was recorded daily. On day 21, three birds from each pen were killed by cervical dislocation and the liver, kidney, and spleen were removed and weighed for relative organ weight assessment. Data were analyzed as a 2x2 full-factorial for AF level and Bio-C using the GLM procedures of SPSS. Our data indicates that Bio-C adsorption capacity was ranged from 29% to 70%, with an average of 44%. In vivo results showed that the performance of birds receiving 0.5 mg/kg AF were not significantly different compared to the control group at any point during the 21-day trial. No main effects were seen on the performance parameters by the inclusion of Bio-C in the diet. There was also no AF/Bio-C interaction. The relative weights of the liver, kidney, and spleen were not significantly different whether birds were fed 0.5 mg/kg AF or 0.4% Bio-C. These data suggest that supplementation of Bio-C has no effect on broiler performance when provided in diets either free of AF or containing up to 0.5 mg/kg.